2015
DOI: 10.1007/s00401-015-1388-1
|View full text |Cite
|
Sign up to set email alerts
|

TREM2 regulates microglial cell activation in response to demyelination in vivo

Abstract: Microglia are phagocytic cells that survey the brain and perform neuroprotective functions in response to tissue damage, but their activating receptors are largely unknown. Triggering receptor expressed on myeloid cells 2 (TREM2) is a microglial immunoreceptor whose loss-of-function mutations in humans cause presenile dementia, while genetic variants are associated with increased risk of neurodegenerative diseases. In myeloid cells, TREM2 has been involved in the regulation of phagocytosis, cell proliferation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
244
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 235 publications
(273 citation statements)
references
References 85 publications
27
244
2
Order By: Relevance
“…TREM2 is expressed in innate immune cells (e.g. dendritic cells and macrophages) implicated in host defense [9] while in the CNS TREM2 is involved in microglia activation and phagocytosis in response to injury [7,42]. Consistently with this, our genetic analyses found an enrichment of pathways involved in virus endocytosis, transport and intracellular vesicular trafficking.…”
Section: Discussionsupporting
confidence: 79%
“…TREM2 is expressed in innate immune cells (e.g. dendritic cells and macrophages) implicated in host defense [9] while in the CNS TREM2 is involved in microglia activation and phagocytosis in response to injury [7,42]. Consistently with this, our genetic analyses found an enrichment of pathways involved in virus endocytosis, transport and intracellular vesicular trafficking.…”
Section: Discussionsupporting
confidence: 79%
“…However, recent work demonstrated that loss of Trem2 leads either to microglial degeneration in different diseases of the central nervous system [55,66,11], or conversely to protection [34]. Thus, the exact mechanisms underlying 5-HT 2B R-mediated regulation of microglial survival and the role of scavenger receptors in this response will have to be investigated in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…In the cuprizone-induced model of demyelinating disease, Trem2-deficient mice presented fewer activated microglia in the corpus callosum compared to wild-type mice; this corresponded to a defect in myelin clearance as well as to an increase in axonal pathology as evidenced from immunohistochemistry [146]. Remyelination after injury in Trem2 KO mice was also impaired, as was the microglial transcriptional response for genes involved in phagocytosis and lipid metabolism [55].…”
Section: Trem2 In Demyelination/remyelinationmentioning
confidence: 96%